The clover root-nodule bacteria (Rhizobium trifolii Dangeard) in soils of the Stellenbosch district - Scheffler, J. G.(Jacobus Gideon) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. Agric.) -- University of Stellenbosch, 1965.